Benefits and Challenges Associated with Using Online Communities by Social Enterprises: A Thematic Analysis of Qualitative Interviews. Issue 2 (4th May 2021) - Abedin, Behnam; Maloney, Brittany; Watson, Jason
Abstract: Social Enterprises (SEs) have gained a considerable amount of attention during last decade in entrepreneurship sector. This paper aims to investigate the benefits and challenges associated with the use of online communities (OCs) by actors in SE sector for value co-creation. Nine semi-structured interviews were conducted with actors derived primarily from 4 Facebook OCs dedicated for SEs. Results demonstrate that the benefits of using OCs include increased accessibility, time and cost effectiveness, increased responsiveness, accessing to a network of connections, and resource exchange opportunities. However, the challenges include time-consuming, budget, lack of capacity, inadequate moderation, fragmentation of efforts, and inactivity.